On the lexicalization of morpheme супер / super in Russian and Polish - Straś, Ewa (Papers in Linguistics, 2020)
This article discusses problems related to distinguishing the morpheme super as an independent lexeme in the systems of Polish and Russian. This process is predominantly facilitated by the semantics of the analysed morpheme, which is borrowed from Latin but is also subjected to the influence of English. Nouns, adjectives and adverbs including the morpheme super, which are intense in their semantic structure, are positively marked, which is directly connected with expressing emotions. However, in the light of the economy of linguistic resources super becomes a convenient tool of expressing positive but very general assessment deprived of further details.